DNA methylation profiling identifies TBKBP1 as potent amplifier of cytotoxic activity in CMV-specific human CD8+ T cells - Yu, Zheng; Sasidharan-Nair, Varun; Buchta, Thalea; Bonifacius, Agnes; Khan, Fawad; Pietzsch, Beate; Ahmadi, Hosein; Beckstette, Michael; Niemz, Jana; Hilgendorf, Philipp; Mausberg, Philip; Keller, Andreas; et al. (PLoS Pathogens, 2024)
Epigenetic mechanisms stabilize gene expression patterns during CD8+ T cell differentiation. Although adoptive transfer of virus-specific T cells is clinically applied to reduce the risk of virus infection or reactivation in immunocompromised individuals, the DNA methylation pattern of virus-specific CD8+ T cells is largely unknown. Hence, we here performed whole-genome bisulfite sequencing of cytomegalovirus-specific human CD8+ T cells and found that they display a unique DNA methylation pattern consisting of 79 differentially methylated regions (DMRs) when compared to memory CD8+ T cells. Among the top demethylated DMRs in cytomegalovirus-specific CD8+ T cells was TBKBP1, coding for TBK-binding protein 1 that can interact with TANK-binding kinase 1 (TBK1) and mediate pro-inflammatory responses in innate immune cells downstream of intracellular virus sensing. Since TBKBP1 has not yet been reported in T cells, we aimed to unravel its role in virus-specific CD8+ T cells. TBKBP1 demethylation in terminal effector CD8+ T cells correlated with higher TBKBP1 expression at both mRNA and protein level, independent of alternative splicing of TBKBP1 transcripts. Notably, the distinct DNA methylation patterns in CD8+ T cell subsets was stable upon long-term in vitro culture. TBKBP1 overexpression resulted in enhanced TBK1 phosphorylation upon stimulation of CD8+ T cells and significantly improved their virus neutralization capacity. Collectively, our data demonstrate that TBKBP1 modulates virus-specific CD8+ T cell responses and could be exploited as therapeutic target to improve adoptive T cell therapies.
CRIS-Team Scopus Importer:2024-10-11